Stage-specific control of stem cell niche architecture in the Drosophila testis by the posterior Hox gene Abd-B - Papagiannouli, Fani; Lohmann, Ingrid (Computational and structural biotechnology journal, 2015)
A fundamental question in biology is how complex structures are maintained after their initial specification. We address this question by reviewing the role of the Hox gene Abd-B in Drosophila testis organogenesis, which proceeds through embryonic, larval and pupal stages to reach maturation in adult stages. The data presented in this review highlight a cell- and stage-specific function of Abd-B, since the mechanisms regulating stem cell niche positioning and architecture at different stages seem to be different despite the employment of similar factors. In addition to its described role in the male embryonic gonads, sustained activity of Abd-B in the pre-meiotic germline spermatocytes during larval stages is required to maintain the architecture of the stem cell niche by regulating βPS-integrin localization in the neighboring somatic cyst cells. Loss of Abd-B is associated with cell non-autonomous effects within the niche, leading to a dramatic reduction of pre-meiotic cell populations in adult testes. Identification of Abd-B target genes revealed that Abd-B mediates its effects by controlling the activity of the sevenless ligand Boss via its direct targets Src42A and Sec63. During adult stages, when testis morphogenesis is completed with the addition of the acto-myosin sheath originating from the genital disc, stem cell niche positioning and integrity are regulated by Abd-B activity in the acto-myosin sheath whereas integrin acts in an Abd-B independent way. It seems that the occurrence of new cell types and cell interactions in the course of testis organogenesis made it necessary to adapt the system to the new cellular conditions by reusing the same players for testis stem cell niche positioning in an alternative manner.